(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Natural death means that the death was caused entirely by the disease, and the trauma or poison did not play any part in its bringing. Cardiovascular system (45-50%) and diseases of the Respiratory system (15-23%) play the role in cause of death. The present study has been undertaken to brighten the light on the pathological conditions present in thoracic cavity and their role in cause of death. Cardiac Pathology 64.47% (n=98) predominates the Pulmonary pathology 32.24% (n=49). Coronary artery disease was the leading cause of death with 46.71% (n=71) followed by Pneumonia in 26.31% of cases (n=40). Significant narrowing (Grade IV) of coronary artery lumen was observed in Left anterior descending (LAD) coronary artery.